2020
DOI: 10.3390/nano10091706
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Electrospun Composite Nanofiber Membrane for Highly Efficient Air Filtration

Abstract: Highly efficient air filtration with low pressure drop is the key to air purification. In this work, a self-powered electrospun nanofiber membrane with an electrostatic adsorption effect was prepared to improve the filtration efficiency of micro/nano particles. The composite membrane was comprised of polyvinyl chloride (PVC) nanofibers and polyamide-6 (PA6) nanofibers. The triboelectric effect between the two adjacent nanofiber membranes generated electrostatic charges under the action of air vibration, by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The results showed that PVC/PVDF nanofibers have a diameter of about 400-800 nm and offer better filtration efficiency compared with HEPA filtration (Figure 6). Shao et al [93] have been combining PVC nanofiber mats and PA6 nanofiber mats to prepare a self-powered air filtration composite membrane. The principal work of this filter is that PVC nanofiber mats will be positively charged and PA6 nanofiber mats will be negatively charged under the action of air currents.…”
Section: Air Filtrationmentioning
confidence: 99%
“…The results showed that PVC/PVDF nanofibers have a diameter of about 400-800 nm and offer better filtration efficiency compared with HEPA filtration (Figure 6). Shao et al [93] have been combining PVC nanofiber mats and PA6 nanofiber mats to prepare a self-powered air filtration composite membrane. The principal work of this filter is that PVC nanofiber mats will be positively charged and PA6 nanofiber mats will be negatively charged under the action of air currents.…”
Section: Air Filtrationmentioning
confidence: 99%
“…Electrospun products have already been studied for many applications such as wound healing [ 12 , 13 ], tissue engineering [ 14 , 15 ], drug-releasing and drug target delivery systems [ 16 , 17 ], sensors [ 18 , 19 ], membranes [ 20 , 21 ], batteries [ 22 , 23 ], solar cells [ 24 , 25 ], catalysts [ 26 , 27 ], protecting clothing [ 28 , 29 ], separation [ 30 ], decommissioning [ 31 ], and environmental remediation [ 32 ]. However, the randomly arranged ultrafine fibers in the electrospun membranes, the high surface area to volume ratios, nano-porosity, good mechanical properties, and vapor permeability of such membranes pre-destined them for filtration membranes and especially for personal protection as face masks against very fine dirt and bacteria, but also viruses with dimensions of about 100 nm [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nanofibers prepared by ES have the characteristics of large specific surface area and high porosity. With the above advantages, electrospinning has been widely used in many fields such as biomedicine, flexible electronics, and filtration membranes [ 8 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%